TRANSFORMATION OF CHARACTER EDUCATION: AN EMERGENCY SOLUTION TO THE CRISIS AND CONTROVERSY OF TEENAGERS' MORALS - Nabilah Hayyu Palupi; Amin Said Husni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study focuses on efforts to transform moral education as a rapid response to challenges and debates surrounding adolescent morality in the digital age. The focus is on evaluating the methods implemented by teachers and schools in integrating moral values into the learning process and their impact on student behavior. This study adopted a qualitative approach with a case study conducted at Nurul Jadid Junior High School in Paiton, Probolinggo. Data were collected through observation, in-depth interviews, and document collection from the principal, teachers, guardians, and students. The findings indicate that the transformation of moral education is carried out through collaborative learning methods, teacher role models, and spiritual habituation activities such as Spirit Morning and Good Character Habits (PKB). This approach successfully forms empathy, politeness, and a sense of social responsibility among students. This study implies that relevant and sustainable moral education can serve as a strategic model for building adolescent character and strengthening moral values in the digital age.